Studies on Schismatoglottideae (Araceae) of Borneo LXX — New colonial species for the Schismatoglottis [Calyptrata Clade] from Sarawak - Wong, Sin Yeng; Boyce, Peter C. (Firenze University Press, 2021)
Three new colonial species of Schismatoglottis Calyptrata clade are described and illustrated from Sarawak and compared with the four pre-existing morphologically similar species occurring in the state. A modi.ed description of Schismatoglottis niahensis is provided to correct a previous misinterpretation of the stem architecture. All seven recognized species are illustrated from living plants.